2002
DOI: 10.1074/jbc.m110693200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Zeaxanthin Is an Obligatory Event in the Regulation of Photosynthetic Light Harvesting

Abstract: By dynamic changes in protein structure and function, the photosynthetic membranes of plants are able to regulate the partitioning of absorbed light energy between utilization in photosynthesis and photoprotective non-radiative dissipation of the excess energy. This process is controlled by features of the intact membrane, the transmembrane pH gradient, the organization of the photosystem II antenna proteins and the reversible binding of a specific carotenoid, zeaxanthin. Resonance Raman spectroscopy has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
94
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 32 publications
(29 reference statements)
11
94
1
1
Order By: Relevance
“…In addition, the measurements of LHCII and thylakoids under the unquenched condition all lack a lifetime component of Ϸ10 ps, which supports the notion that one-photon excitation of Zea is also unlikely when it is bound in a protein environment. All of the results are consistent with the idea that an electronic modification of some Zea molecules during the induction of qE, most likely in PsbS itself, is responsible for our observations (37).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, the measurements of LHCII and thylakoids under the unquenched condition all lack a lifetime component of Ϸ10 ps, which supports the notion that one-photon excitation of Zea is also unlikely when it is bound in a protein environment. All of the results are consistent with the idea that an electronic modification of some Zea molecules during the induction of qE, most likely in PsbS itself, is responsible for our observations (37).…”
Section: Discussionsupporting
confidence: 81%
“…The first is that the probe wavelengths from 530 to 580 nm are located on the red side of the spectrally red-shifted Zea absorption (37). For a given probe wavelength, pr , and a symmetric S 0 3 S 2 absorption band with an absorption maximum m , a band shift ϽϷ2͉ pr Ϫ m ͉ will lead to increased absorption.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo light absorption and resonant Raman experiments on quenched PSII in leaves and chloroplasts indicated that zeaxanthin undergoes dramatic spectroscopic changes upon induction of feedback deexcitation: its absorption maximum shifts to the red by at least 22 nm, and the molecule assumes a very specific, highly twisted conformation (35). To account for these phenomena, Ruban et al (35) proposed that zeaxanthin is bound in a highly polarizing local environment, possibly arising from a strong electric field of a dipole or charge in the zeaxanthin vicinity. It seems plausible that such an extensive change of local environment, combined with a distortion of the polyene backbone, may bring down ICT states of zeaxanthin to couple with S 1 , and thereby activate a quenching mechanism similar to that reported here for the model systems.…”
Section: Discussionmentioning
confidence: 99%
“…The light Ϫ dark recovery absorption difference spectrum is characterized by a series of positive and negative bands, the best-known of which is ⌬A535 (20). Using resonance Raman the origin of ⌬A535 was shown to be a sub-population of red-shifted zeaxanthin molecules (21). In the absence of zeaxanthin (and antheraxanthin) a proportion of NPQ remains and the ⌬A535 change is blue-shifted to 525 nm (⌬A525) (22).…”
mentioning
confidence: 99%